2004
DOI: 10.1002/cncr.20531
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of immunophenotype in a retrospective comparative study of 297 peripheral T‐cell lymphomas, unspecified, and 496 diffuse large B‐cell lymphomas

Abstract: BACKGROUND To assess the impact of T‐cell/B‐cell phenotype on clinical outcome, the authors retrospectively compared patients who had peripheral T‐cell lymphoma, unspecified (PTCL‐U), with patients who had diffuse large B‐cell lymphoma (DLBCL). METHODS Two hundred ninety‐seven cases of PTCL‐U and 496 cases of DLBCL that had been transferred from the files of the Intergruppo Italiano Linfomi or the Gruppo Italiano Linfomi were integrated into a unique working file and reviewed by the authors. RESULTS The PTCL‐U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
0
37
1
Order By: Relevance
“…The regimen of cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) remains the most commonly used chemotherapeutic treatment for PTCL. However, CHOP has poor efficacy, a low CR rate (10%-60%) and a median overall survival (OS) of <3 years [5][6][7] . Moreover, doxorubicin has a low therapeutic index and significant treatment-related toxicities, whereas pegylated liposomal doxorubicin (PLD) has a stable spatial structure and demonstrates reduced binding to plasma proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The regimen of cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP) remains the most commonly used chemotherapeutic treatment for PTCL. However, CHOP has poor efficacy, a low CR rate (10%-60%) and a median overall survival (OS) of <3 years [5][6][7] . Moreover, doxorubicin has a low therapeutic index and significant treatment-related toxicities, whereas pegylated liposomal doxorubicin (PLD) has a stable spatial structure and demonstrates reduced binding to plasma proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The disease-free and overall survival times of patients with PTCL-u following conventional CHOP treatment are markedly lower than those of patients with B-cell lymphoma (30,31). Novel therapeutic approaches aiming to improve upon the short-term and long-term efficacy of the currently available PTCL-u treatments are being investigated at present.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In Western countries, by contrast, high-risk groups account for only 42-46% of patients with PTCL. 2,9,17 Although the IPI for PTCLs appears to be higher in Japan than in Western countries, international studies with large patient populations will be required to confirm the racial differences in the clinical characteristics of PTCLs.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Moreover, Morabito et al reported that, although the OS curves associated with the Tcell and B-cell immunophenotypes significantly differed from each other (5-year OS, 42% vs. 56% ; median OS, 39 months vs. 94 months, P=0.0012), multivariate analysis did not detect an association between OS and immunophenotype. 17 It seems likely that we were able to identify immunophenotype as an independent risk factor because we excluded patients with ALCL, which have more favorable outcomes than those with PTCL-u, and we compared nodal PTCLs with nodal DLBCL treated with the same standard CHOP regimen. Moreover, although they were small patient populations, we compared OS among patients with a high IPI index (14 of PTCLs, 10 of DLBCL).…”
Section: Figmentioning
confidence: 99%